2012
DOI: 10.1186/1471-213x-12-39
|View full text |Cite
|
Sign up to set email alerts
|

Standardised classification of pre-release development in male-brooding pipefish, seahorses, and seadragons (Family Syngnathidae)

Abstract: BackgroundMembers of the family Syngnathidae share a unique reproductive mode termed male pregnancy. Males carry eggs in specialised brooding structures for several weeks and release free-swimming offspring. Here we describe a systematic investigation of pre-release development in syngnathid fishes, reviewing available data for 17 species distributed across the family. This work is complemented by in-depth examinations of the straight-nosed pipefish Nerophis ophidion, the black-striped pipefish Syngnathus abas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 25 publications
1
41
0
Order By: Relevance
“…We further examined the expression levels during the development of messmate pipefish embryo, whose developmental stages were used according to the Sommer et al (). As shown in Figure B, HCE genes were strongly expressed in embryonic shield to eye pigmentation stage embryos, and quite weakly in protruding snout stage and just before newborn embryos.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We further examined the expression levels during the development of messmate pipefish embryo, whose developmental stages were used according to the Sommer et al (). As shown in Figure B, HCE genes were strongly expressed in embryonic shield to eye pigmentation stage embryos, and quite weakly in protruding snout stage and just before newborn embryos.…”
Section: Resultsmentioning
confidence: 99%
“…However, in seahorse embryos, only HCE gene expression was detected, supporting the above results that the LCE gene was pseudogenized and was not active anymore in seahorses. We further examined the expression levels during the development of messmate pipefish embryo, whose developmental stages were used according to the Sommer et al (2012). As shown in Figure 5B, HCE genes were strongly expressed in embryonic shield to eye pigmentation stage embryos, and quite weakly in protruding snout stage and just before newborn embryos.…”
Section: Semi-quantitative Analysis Of Hatching Enzyme Gene Expressionmentioning
confidence: 99%
“…Such embryogenesis is a long process where duration differs among species, particularly when comparing tropical v . temperate species (Novelli et al ., ; Silveira & Fontoura, ; Sommer et al ., ; Wetzel & Wourms, ).…”
Section: Discussionmentioning
confidence: 99%
“…Seahorse eggs hatch before embryogenesis is complete, with the embryos remaining inside the male's brood pouch until full yolk resorption (Wetzel & Wourms, ). Hatched embryos continue developing inside the male pouch for several days before they are released (Sommer et al ., ). Embryonic and larval (post‐hatch–pre‐release) periods overlap in seahorse species and free‐swimming offspring emerge later from the pouch (Kornienko, ; Pham et al ., ; Wetzel & Wourms, ).…”
Section: Introductionmentioning
confidence: 99%
“…Body size is a key fitness correlate in S. typhle, both in adults and in juveniles. Because by parturition the yolk sacs have usually been fully resorbed (Sommer et al, 2012), juveniles switch to external feeding once released from the paternal brood pouch. A previous study has shown that larger juvenile size at birth is associated both with subsequent faster growth rates, presumably due to higher foraging success, and with higher survival, due to greater success at escaping predators (Ahnesjö, 1992a).…”
Section: Discussionmentioning
confidence: 99%